Helicobacter pylori and Epstein–Barr Virus Infection in Gastric Diseases: Correlation with IL-10 and IL1RN Polymorphism. (6th December 2019) - Teresa, Fasciana; Serra, Nicola; Capra, Giuseppina; Mascarella, Chiara; Gagliardi, Cesare; Di Carlo, Paola; Cannella, Sara; Simonte, Maria Rosa; Lipari, Dario; Sciortino, Miriam; Scola, Letizia; Giammanco, Anna
Abstract : Introduction . Helicobacter pylori and Epstein–Barr virus (EBV) infection have recently been shown to be associated with gastric diseases. Polymorphisms in genes encoding cytokines such as interleukin 10 (IL-10) and interleukin 1 Receptor (IL-1RN) influence cytokine secretion levels and appear to contribute to the risk of developing gastroduodenal diseases. To our knowledge, this is the first preliminary study to address the association of coinfection with H. pylori and EBV and their correlation with genetic predisposition in the development of gastric diseases. Methods . Gastric biopsy samples of 96 patients with different gastric diseases were used. Results . Our results showed that the rate of coinfection was higher in patients with gastric cancer than in patients with normal gastric mucosa, active chronic gastritis, and MALT lymphoma. As regards the characterization of H. pilory strains, the polymorphism s1m1i1 of vacA gene was more frequent in patients with MALT Lymphoma in comparison to others, while the polymorphism s2m2i2 was most frequent in patients with normal gastric mucosa. In addition, patients who tested positive for the cagA gene were more frequently those affected with gastric cancer than those with inactive chronic gastritis. Similarly, the patients with oipA gene ON were more frequently those with gastric cancer than those with inactive chronic gastritis. Conclusion . According to our analysis, there was no correlation between coinfection and polymorphisms in genes encoding IL-10 and IL-1RN. We conclude that various factors can be involved in the development of gastric diseases.